2004
DOI: 10.1086/420739
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pharmacodynamic End Points in the Evaluation of Gatifloxacin for the Treatment of Acute Maxillary Sinusitis

Abstract: The relationship between drug exposure and the time course of antimicrobial effect at the primary infection site for acute maxillary sinusitis has not previously been explored. This single-center, open-label study quantified the time course of sinus sterilization, described gatifloxacin exposure at the infection site, and posed the hypothesis that the use of continuous and quantitative time-related end points may allow for better characterization of drug effect with fewer patients than traditional clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Fluoroquinolones usually achieve tissue and body fluid concentrations that are higher than those of most β-lactams due to their physicochemical properties [68,69,70,71,72,73,74]. Our group applied body fluid penetration models for other quinolones and β-lactams [75,76,77,78,79,80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones usually achieve tissue and body fluid concentrations that are higher than those of most β-lactams due to their physicochemical properties [68,69,70,71,72,73,74]. Our group applied body fluid penetration models for other quinolones and β-lactams [75,76,77,78,79,80,81].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ambrose et al (3) showed that in patients with acute maxillary sinusitis attributable to Streptococcus pneumoniae, high-dose gatifloxacin resulted in sinus sterilization within 24 to 72 h after the initiation of therapy. The median sinus gatifloxacin AUC/MIC ratio in these patients was 122.8.…”
Section: The Inoculum Effect and Importance Of A Short Time To Treatmentmentioning
confidence: 99%
“…doi:10.1016/j.ijantimicag.2008.01.027 Table 1 Collection times of blood and sinus aspirate First cohort of six subjects Second cohort of three subjects Thirteen sinus aspirate and blood samples were collected: 0 (pre first dose), 1, 2, 3, 4, 6, 8, 12, 24, 48, 72, 96 and 120 h post first dose Seven sinus aspirate and blood samples were collected: 0 (pre first dose), 2, 4, 12, 24, 48 and 72 h post first dose drug assay over time using an indwelling sinus catheter [8]. To date, we are aware of only two other studies that have used this technique [8,9], therefore this study provides a unique insight into the pharmacokinetics of azithromycin in sinus fluid. In this trial, the pharmacokinetics of a single 2.0 g oral dose of AZ-ER versus AZ-IR 500 mg given orally once daily for 3 days was characterised in subjects with ABS using an indwelling sinus catheter (SinoJect ® ; Atos Medical AB, Hörby, Sweden).…”
Section: Introductionmentioning
confidence: 99%